Association between alcohol consumption and hepatic fibrosis in Chinese adult males with metabolic dysfunction-associated steatotic liver disease - Li, Mao; Yu, Bin; Zhang, Xiaoli; Pan, Jia; Tang, Lei; Zhang, Yi; Wang, Ruixin; Zeng, Honglian; Yang, Shujuan (Frontiers in Medicine, 2025)
BackgroundThe impact of moderate drinking on the risk of liver fibrosis in non-alcoholic fatty liver disease (NAFLD) remains controversial worldwide. Notably, China, with the fastest-growing incidence of NAFLD and the highest number of alcohol-attributable deaths globally, has relatively few studies addressing this issue. This study aimed to explore the association between alcohol consumption and liver fibrosis in Chinese men with metabolic dysfunction-associated steatotic liver disease (MASLD).MethodsWe recruited 4,683 male employees diagnosed with MASLD from southwest China, including 4,287 with pure MASLD and 396 with metabolic and alcohol-related liver disease (MetALD) who consumed increased alcohol (30-60 g/d). Advanced fibrosis was defined as a fibrosis-4 index (FIB-4) ≥ 2.67, and FIB-4 ≥ 1.30 indicated an intermediate/high probability of hepatic fibrosis. Logistic regression models were used to assess the association between alcohol consumption and hepatic fibrosis, and analyze the modification effect of body mass index (BMI) and waist-to-hip ratio (WHR) on the association. Propensity score matching method was used to test the robustness of the regression results.ResultsCompared with non-drinkers, both moderate (OR = 3.02, 95% CI: 1.16-10.31) and increased alcohol consumption (OR = 4.64, 95% CI: 1.60-16.82) were significantly associated with an increased risk of advanced fibrosis in males with MASLD. Additionally, moderate (OR = 1.33, 95% CI: 1.07-1.66) and increased drinking (OR = 1.74, 95% CI: 1.28-2.34) were associated with intermediate/high probability of hepatic fibrosis, with similar results from logistic regression analysis in propensity score-matched cases. Trend analysis revealed the risk of hepatic fibrosis increased with increasing alcohol intake (FIB-4 ≥ 1.30, p for trend < 0.001; FIB-4 ≥ 2.67, p for trend = 0.007). Further subgroup analysis showed that the association between moderate drinking and intermediate/high probability of hepatic fibrosis was predominantly observed in males with BMI ≥ 23 kg/m2 (OR = 1.35, 95% CI: 1.08-1.69) and those with WHR ≥ 0.9 (OR = 1.40, 95% CI: 1.11-1.78).ConclusionIn China, moderate alcohol intake may heighten the risk of hepatic fibrosis in males with MASLD who are overweight/obese or have abdominal obesity. Moreover, males with MetALD may have a higher risk of fibrosis compared to those with pure MASLD.